The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3389/fnhum.2013.00515
|View full text |Cite
|
Sign up to set email alerts
|

The social regulation of threat-related attentional disengagement in highly anxious individuals

Abstract: Social support may normalize stress reactivity among highly anxious individuals, yet little research has examined anxious reactions in social contexts. We examined the role of both state and trait anxiety in the link between social support and the neural response to threat. We employed an fMRI paradigm in which participants faced the threat of electric shock under three conditions: alone, holding a stranger's hand, and holding a friend's hand. We found significant interactions between trait anxiety and threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Given the strong correlation between (reciprocally transformed) BAI scores and SDS scores [r (74) = -0.73, p < 0.001, Fig.6a], we explored distinct brain networks between 2 1 anxiety and depression. The two-sample t-test revealed a significant difference between "anxiety scores" and "depression scores" [t (38) = -4.15, p <0.001, Cohen's d = -1.857, Fig. 6c], validating significant differences between the anxiety-specific and the depression-specific networks.…”
Section: Distinct Brain Network Between Anxiety and Depressionmentioning
confidence: 81%
See 1 more Smart Citation
“…Given the strong correlation between (reciprocally transformed) BAI scores and SDS scores [r (74) = -0.73, p < 0.001, Fig.6a], we explored distinct brain networks between 2 1 anxiety and depression. The two-sample t-test revealed a significant difference between "anxiety scores" and "depression scores" [t (38) = -4.15, p <0.001, Cohen's d = -1.857, Fig. 6c], validating significant differences between the anxiety-specific and the depression-specific networks.…”
Section: Distinct Brain Network Between Anxiety and Depressionmentioning
confidence: 81%
“…Among the prefrontal-limbic circuit, vACC, vlPFC and PCC were key nodes that contributed to the anxiety-predictive model. vACC plays a key role in the modulation of physiological arousal (Maresh et al, 2013) and the control of negative affect (LeDoux, 2003;Passamonti et al, 2008;Petrovic et al, 2005). vlPFC has been implicated in effortful down-regulation of negative emotion (Campbell-Sills et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst not examining it from a domains based perspective, previous research using brain imaging has focused on how threat regulation may be modulated differently depending on the presence of someone else (Coan et al, 2017;Coan, Kasle, Jackson, Schaefer, & Davidson, 2013;Coan, Schaefer, & Davidson, 2006;Eisenberger et al, 2011;Kawamichi, Kitada, Yoshihara, Takahashi, & Sadato, 2015;Maresh, Beckes, & Coan, 2013;Younger, Aron, Parke, Chatterjee, & Mackey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, neural activation patterns during threat of shock tasks are further influenced by relationship quality and mutuality, such that better relationship quality and mutuality between romantic partners was associated with reduced activation in threat and pain-related regions when holding the hand of romantic partners (Coan et al, 2006), and increased activation in safety signalling regions when viewing pictures of romantic partners (Eisenberger et al, 2011). Recent studies have also shown modulation of neural responses to threat when holding the hand of a friend (Kawamichi, Kitada, Yoshihara, Takahashi, & Sadato, 2015;Maresh, Beckes, & Coan, 2013). In these studies, holding the hand of friend compared to rubber hand or the hand of a stranger has been shown to suppress visual cortex activity to negative stimuli (Kawamich, Kitada, Yoshihara, Takahashi, & Sadato, 2015), as well as enhance activity in threat-related brain regions associated with engagement in anxious individuals (Maresh, Beckes, & Coan, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the precuneus also showed increased activation when viewing with a friend compared to alone and this region is particularly associated with self-related thoughts and self-referential processing, (Cavanna and Trimble, 2006;Northoff et al, 2006). This might indicate a neural mechanism whereby sharing with close others also engages self-involvement (Müller-Pinzler et al, 2015;Maresh et al, 2013). Importantly, the friend sharing effect on increasing positive valence relative to the alone condition was significantly enhanced by OXT in female but not male subjects.…”
Section: Discussionmentioning
confidence: 87%